Helsinki VideoMEG Project: Augmenting magnetoencephalography with synchronized video recordings - Zhdanov, Andrey (MethodsX, 2018)
The primary goal of the Helsinki VideoMEG Project is to enable magnetoencephalography (MEG) practitioners to record and analyze the video of the subject during an MEG experiment jointly with the MEG data. The project provides: • Hardware assembly instructions and software for setting up video and audio recordings of the participant synchronized to MEG data acquisition. • Basic software tools for analyzing video and audio together with the MEG data. The resulting setup allows reliable recording of video and audio from the subject in various real-world usage scenarios. The Helsinki VideoMEG Project allowed successful establishment of video-MEG facilities in four different MEG laboratories in Finland, Sweden and the United States.